Towards a new model of management and self-funding to regenerate obsolete neighborhoods (Ciudades, 2017)
The article addresses the problem of financing of the integral regeneration of neighborhoods. After the analysis of already tested models of management and financing, guidelines for a new model based on cooperativism are proposed. The economic potential of an active and unitary collective action requires a social economy model based on the provision of services as a basis for habitability and maintenance as an objective to reduce cycles of obsolescence. This articulates a long-term mechanism that transcends the single action of rehabilitation and ensures a progressive adaptation to new standards of habitability.
Keywords: cohousing; cooperatives; collaborative economy; provision of services; neighborhood regeneratio